Problematic points of anticoagulant therapy for atrial fibrillation in certain Russian regions in 2016- 2019: results of a retrospective big data analysis - M. A. Druzhilov; O. Yu. Druzhilova; Z. A. Ilchenko; P. I. Chalaya; T. Yu. Kuznetsova (Российский кардиологический журнал, 2024)
Aim. This retrospective analysis of anticoagulant therapy prescription rate in patients with atrial fibrillation (AF) aged ³18 years in certain Russian regions in 20162019 using artificial intelligence technologies.Material and methods. Anonymized data of patients with AF aged ³18 years (n=144431; men, 42,0%; mean age, 68,9±15,7 years; mean CHA2DS2-VASc score, 3,2±1,8) were extracted from the Webiomed predictive analytics service using continuous sampling from electronic health records in medical facilities of 6 Russian constituent entities (Republic of Bashkortostan, Republic of Buryatia, Republic of Karelia, Republic of Sakha (Yakutia), Perm Krai, Yamalo-Nenets Autonomous Okrug) for 2016-2019 using artificial intelligence technologies. Results. Anticoagulant therapy prescription rate in the total sample was 29,7%. Patients with AF and a high thromboembolism risk received anticoagulants in 34,8% of cases. Anticoagulant therapy was prescribed significantly less frequently to women with AF compared to men. In the subgroup of individuals aged under 75 years, anticoagulant therapy prescription rate with a high thromboembolism risk exceeded the same indicator in the subgroup of individuals aged ³75 years as follows: 41,2% vs 29,6% (p<0,001). In patients with AF under 75 years and a high thromboembolism risk, anticoagulant therapy prescription rate significantly gained with an increase in the number of points on the CHA2DS2-VASc scale in the range from 33,2% to 61,9%, in patients aged ³75 years — in the range from 13,0% to 55,5%. We revealed that 23317 (16,1%) patients were prescribed direct oral anticoagulants, of which 9,655 (41,4%) patients initially received warfarin.Conclusion. The study results indicate an unsatisfactory anticoagulant therapy prescription rate in patients with AF and a high thromboembolism risk in certain Russian regions in 2016-2019. Despite its growth with a CHA2DS2-VASc score increase in the high-risk range, it did not comply with current clinical guidelines This specifies the need for stricter control over the implementation of treatment and diagnostic algorithms and local protocols for managing these patients.